1983
DOI: 10.1271/bbb1961.47.243
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformation of the labdanes, cis-abienol and sclareol.

Abstract: The microbial transformation of ds-abienol and sclareol by a recently isolated soil bacterium, JTS-131, was studied. In the presence of metabolic inhibitors, three newcompoundswere isolated from the culture broth as degradation products of cw-abienol. They were determined to be (12Z)labda-12,14-dien-18-ol, (12Z)-labda-12,14-dien-18-oic acid and its methylester. Two new compounds were also formed from sclareol in the presence of metabolic inhibitors. They were determined to be 13/Miydroxylabd-14-en-18-oic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…It was also observed that Fusarium lini converted sclareol into 1β-hydroxysclareol ( 381 ) and (12 S )-12-hydroxysclareol ( 382 ) in 1.3% and 1% yield, respectively (Table ) . In 1983, Hieda and co-workers found that the microorganism Rhodococcus erythropolis JTS-131 produces two exclusive products from sclareol, 13β-hydroxylabd-14-en-18-oic acid ( 379 ) and 13β-hydroxylabd-14-en-18-oic acid methyl ester ( 380 ), in about 2 days (Table ) …”
Section: Biotransformationmentioning
confidence: 97%
See 1 more Smart Citation
“…It was also observed that Fusarium lini converted sclareol into 1β-hydroxysclareol ( 381 ) and (12 S )-12-hydroxysclareol ( 382 ) in 1.3% and 1% yield, respectively (Table ) . In 1983, Hieda and co-workers found that the microorganism Rhodococcus erythropolis JTS-131 produces two exclusive products from sclareol, 13β-hydroxylabd-14-en-18-oic acid ( 379 ) and 13β-hydroxylabd-14-en-18-oic acid methyl ester ( 380 ), in about 2 days (Table ) …”
Section: Biotransformationmentioning
confidence: 97%
“…142 In 1983, Hieda and co-workers found that the microorganism Rhodococcus erythro- a The partially purified metabolites were acetylated using standard conditions to afford products 396 and 397. polis JTS-131 produces two exclusive products from sclareol, 13β-hydroxylabd-14-en-18-oic acid (379) and 13β-hydroxylabd-14-en-18-oic acid methyl ester (380), in about 2 days (Table 2). 143…”
Section: Sclareolmentioning
confidence: 99%
“…Terpene skeleton is most favourable for structural modification by microbes. Numerous publications described already microbial transformation of terpenoids (Bock et al, 1988;Bock et al, 2006;Ishida, 2005;Joglekar et al, 1969;Welf-Rainer-Abraham et al, 1986;Hieda et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…There are no reports concerned with the mammalian metabolism of isocupressic acid ( 1 ). However, microbial transformations have been reported for labdane-diterpenes, including sclareol [labd-14-ene-8α,13β-diol] and its analogues, , and with ruminal metabolism of isocupressic acid ( 1 ) …”
mentioning
confidence: 99%